2008
DOI: 10.1152/ajpcell.00368.2007
|View full text |Cite
|
Sign up to set email alerts
|

Acetoacetate and β-hydroxybutyrate in combination with other metabolites release insulin from INS-1 cells and provide clues about pathways in insulin secretion

Abstract: Mitochondrial anaplerosis is important for insulin secretion, but only some of the products of anaplerosis are known. We discovered novel effects of mitochondrial metabolites on insulin release in INS-1 832/13 cells that suggested pathways to some of these products. Acetoacetate, beta-hydroxybutyrate, alpha-ketoisocaproate (KIC), and monomethyl succinate (MMS) alone did not stimulate insulin release. Lactate released very little insulin. When acetoacetate, beta-hydroxybutyrate, or KIC were combined with MMS, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 37 publications
4
43
0
Order By: Relevance
“…These rates are comparable to those for the utilization of 2.8 mM glucose by these cells (332). It should be noted that INS-1 832/13 cells can produce acetoacetylCoA and utilize ␤-hydroxybutyrate and acetoacetate (318,320), raising the possibility that ketone bodies could be produced by ␤-oxidation, in which case label from 14 Clabeled palmitate would not be liberated stoichiometrically as 14 CO 2 .…”
Section: E Fatty Acidssupporting
confidence: 62%
See 1 more Smart Citation
“…These rates are comparable to those for the utilization of 2.8 mM glucose by these cells (332). It should be noted that INS-1 832/13 cells can produce acetoacetylCoA and utilize ␤-hydroxybutyrate and acetoacetate (318,320), raising the possibility that ketone bodies could be produced by ␤-oxidation, in which case label from 14 Clabeled palmitate would not be liberated stoichiometrically as 14 CO 2 .…”
Section: E Fatty Acidssupporting
confidence: 62%
“…The amino acid can be trans-deaminated to ␣-ketoisocaproate (␣KIC) which can ultimately be metabolized to AcCoA and acetoacetate and is thus a potential bioenergetic substrate, in addition to ability to activate glutamate dehydrogenase. ␣KIC is an effective secretagogue in combination with methyl succinate (318,321), although it has been reported to be less effective than glucose in increasing NAD(P)H reduction or hyperpolarizing the mitochondria (400).…”
Section: Arginine and Leucinementioning
confidence: 99%
“…Medium-chain fatty acids, generated by MCT hydrolysis, are metabolized rapidly in mitochondria and yield a large amount of acyl-CoA, which is converted to ketone bodies and released to the blood (30). MacDonald et al reported that b-hydroxybutyrate potentiated glucose-induced insulin release in fresh rat pancreatic islets (31). In the present study, the plasma glucose level might be higher than for fasting rats because the rats were killed without food deprivation.…”
Section: Discussionmentioning
confidence: 56%
“…Pyruvate has long been recognized to be an effective secretagogue in insulinoma cells possessing increased monocarboxylate transporter levels (17,45,46). As well as pyruvate, the cellpermeant methyl succinate (37,45), dihydroxy acetone (17), ␤-hydroxybutyrate (47), acetoacetate (47), ␣-ketoisocaproate (46), and glycerol (17), separately or in combination, are effective secretagogues.…”
Section: Discussionmentioning
confidence: 99%